The main aspects of militia reorganisation in the early 1960s (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article highlights the main directions of militia transformation after the 1962 reorganisation of the republican Ministry of Internal Affairs of the USSR into the republican Ministry of Public Order Protection of the USSR. This transformation was not a simple change of name of this institution and its local bodies. This transformation was in line with the political and ideological views of the then leadership of the state. In fact, it was a change in the concept of law enforcement. According to the leaders of the state, in the context of the “widespread construction of communism”, the main task of the militia was to protect public order with the support of the active part of the population. It was unreasonably believed that crime in the country would steadily decrease, so the scope of militia activities in this area would be less than before. It also envisaged a weakening of the punitive function of the state, less use of violence, and an emphasis on raising the cultural level of militia officers and the population. At the same time, the role of the militia in conducting preliminary investigations was increased, which indicated that the functions of the militia in combating crime were somewhat expanded. The main tasks of the Ministry of Public Order of the Ukrainian SSR are revealed: ensuring public order, preventing and solving crimes. The article shows how the following main methods of improving the work of the militia were implemented: strengthening control over the lives of militia officers outside of working hours; holding cultural and sports events, political agitation and propaganda; and individual training activities. The sphere of activity of the State Automobile Inspection was clarified and specified, which had a generally positive impact on improving road safety. Certain steps towards democratisation of the militia taken at this time did not mean that the Communist Party’s control over this body was weakened. The legal regulation of law enforcement activities remained, as before, entirely within the purview of the Communist Party and its local representatives.
Keywords: Ukraine; 1960s; partial liberalisation of the Soviet political regime; Ministry of Public Order; militia.